Clinical and pharmacoeconomic profile of esomeprazole in acid-related diseases - Zaniolo, Orietta (Farmeconomia. Health economics and therapeutic pathways, 2006)
Protonic pump inhibitors (PPIs) are the most prescribed drugs for acute and maintenance therapy of gastroesophageal reflux disease, H. pylori-eradication (in association with antibacterial therapy), for ulcers prevention and cure and, recently, for prevention of NSAIDs-induced gastropathy. The high prevalence of these acid-related disorders induces a large consumption of PPIs; actually, they are the first drug class in terms of National Health Service pharmaceutical expenditure. This widespread and gradually increasing use enforces the need of a rational assessment of their impact on health care resources. This paper provides an updated profile of esomeprazole, the first PPI developed as a pure isomer, which property involves an advantageous metabolism, resulting in enhanced delivery to the proton pump compared with racemic omeprazole. Several studies showed that the success rate for healing reflux esophagitis is greater for esomeprazole than for omeprazole and some other PPIs. According to an Italian pharmacoeconomic model, esomeprazole therapy for erosive esophagitis is associated with higher benefits and lower costs as compared to omeprazole and pantoprazole. For long-term management of non-erosive gastroesophageal reflux disease, on-demand approach with esomeprazole shows clinical outcomes similar to daily treatment regimens, with substantial cost-saving. Furthermore, esomeprazole is the only PPI approved for 1-week triple therapy for both the eradication and the healing of H. pylori-associated duodenal ulcer, while the other PPIs registered the indication for H. pylori-eradication and, separately, a dosing scheme for ulcer healing (independently from etiology).